Urgensi Metode Belajar dalam Pembelajaran Bahasa Arab (Bagi Penutur Non-Arab) - Ahmad Nahidl Silmy; Rahmat Hidayat Lubis; Yusvita Kusuma Wardani; Shara; Annisaa Ismahani (Mantiqu Tayr: Journal of Arabic Language, 2024)
Learning Arabic for non-native speakers has become an important topic in the era of globalization. Arabic has a very important role in the application and understanding of the Islamic religion, as well as understanding various scientific works and Arabic literature. Therefore, the urgency of effective and efficient learning methods for non-native speakers is very important. The development of research on Arabic language learning methods has progressed in the last few decades. Various methods and approaches have been developed to help non-native speakers effectively and easily. The methods used include information and communication technology, project-based learning, language games, and interactive multimedia. The importance of appropriate learning methods in learning Arabic lies in the method's ability to facilitate understanding and mastery of important aspects of the Arabic language, such as vocabulary, speaking skills, grammar, reading, listening and writing. In this abstract we will discuss the urgency of learning methods. in learning Arabic for non-native speakers, and the importance of using effective and efficient methods. For future researchers, they can develop their learning strategies and they can be regenerated to be more complete for further research. Researchers suggest that future research places more emphasis on implementation and focuses on increasing the achievement of the values ​​and ultimate goals of good Arabic language learning.